2016
DOI: 10.1136/tobaccocontrol-2016-053012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cigarette tax avoidance and evasion: evidence from a national sample of littered packs

Abstract: IntroductionA number of recent studies document the proportion of all cigarette packs that are ‘contraband’ using discarded packs to measure tax avoidance and evasion, which we call tax non-compliance. To date, academic studies using discarded packs focused on relatively small geographical areas such as a city or a neighbourhood.MethodsWe visited 160 communities across 38 US states in 2012 and collected data from littered cigarette packs as part of the State and Community Tobacco Control (SCTC) Research Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
13
2
Order By: Relevance
“…When no attempt is made to purchase untaxed or counterfeit cigarettes, the vast majority of standard tobacco retailers appear to be selling properly taxed cigarette packs that do not show indications of product counterfeiting. Our national results contrast sharply with cigarette pack litter studies from high tax jurisdictions ( Davis et al, 2014 , Consroe et al, 2016 , Merriman, 2010 , Chernick and Merriman, 2013 ); a national cigarette pack litter study, which found 18.5% of packs indicated tax avoidance or tax evasion ( Barker et al, 2016 ); and, from a national pack mail-in study ( Fix et al, 2014 ), which found that state tax stamps did not match with the participants' state of residence for 20% of 686 packs mailed in by participants in the International Tobacco Control United States Survey. Our results suggest each of these may be picking up legal consumer tax avoidance behavior as well as smuggling, as well as possible purchase from illicit sources (e.g., individual sales) ( Fix et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…When no attempt is made to purchase untaxed or counterfeit cigarettes, the vast majority of standard tobacco retailers appear to be selling properly taxed cigarette packs that do not show indications of product counterfeiting. Our national results contrast sharply with cigarette pack litter studies from high tax jurisdictions ( Davis et al, 2014 , Consroe et al, 2016 , Merriman, 2010 , Chernick and Merriman, 2013 ); a national cigarette pack litter study, which found 18.5% of packs indicated tax avoidance or tax evasion ( Barker et al, 2016 ); and, from a national pack mail-in study ( Fix et al, 2014 ), which found that state tax stamps did not match with the participants' state of residence for 20% of 686 packs mailed in by participants in the International Tobacco Control United States Survey. Our results suggest each of these may be picking up legal consumer tax avoidance behavior as well as smuggling, as well as possible purchase from illicit sources (e.g., individual sales) ( Fix et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The NAM report and other studies, however, suggest substantial regional variation, with higher rates of illicit cigarettes in high-tax jurisdictions ( Reuter and Majmundar, 2015 , Barker et al, 2016 , Fix et al, 2014 ), a pattern that we did not observe. Our study does not assess non - retail purchases (e.g., Internet, street corner) of untaxed or counterfeit cigarettes, nor does it assess purposeful attempts to buy untaxed or counterfeit cigarettes at retailers.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the methodologies identified by the assessments can and have been used effectively by multiple non-industry sources. For example, EPS have been the focus of several well-executed measurements of tax avoidance and evasion by independent researchers8–10; much of what is known about adult users of illicit tobacco is based on self-reported information collected through both large population and localised surveys3; econometric modelling has been used extensively to measure ITT, primarily in the USA, for decades3 and a tax gap approach is currently used by the UK government to estimate levels of ITT 11–15…”
Section: Discussionmentioning
confidence: 99%
“…Collecting discarded cigarette packs has been used predominantly in the United States as a method to measure illicit trade [1], [2], [3], [4]. However, there are incidences of studies being done in low- and middle-income countries (LMICs), specifically Poland [5] and South Africa [6].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%